USE OF ANALYTIC HIERARCHY PROCESS IN LOGISTICS DEMAND FORECASTING: USE OF ANALYTIC HIERARCHY PROCESS IN LOGISTICS DEMAND FORECASTING - Bogdanov , Andrey (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The report analyzes the possibility of using analytic hierarchy process in logistics demand forecasting. It proposes a method to estimate parameters of the individual values of the analysis.